Sepsis and AKI in ICU Patients: The Role of Plasma Biomarkers - Paolo Lentini; Massimo de Cal; Anna Clementi; Angela D'Angelo; Claudio Ronco (Critical Care Research and Practice)
Given the higher mortality rate of ICU patients with sepsis and AKI, we decided to investigate the possible correlation between serum biomarkers of organ damage, and endotoxin activity in ICU septic patients. Ninety-eight consecutive adult patients were enrolled in this study. Patients were divided in two groups depending on the presence of sepsis. Fifty-six patients had sepsis, while forty-two patients were nonseptic. Among septic patients, twenty-four subjects developed AKI, while thirty-two did not. AKI occurred in fourteen patients without sepsis as well. The levels of NGAL, BNP, and AOPP were significantly higher among septic patients compared with nonseptic subjects (P<0.001). Among septic patients, subjects who developed AKI showed significant higher levels of NGAL and AOPP (P=0.0425) and BNP (P=0.0327). Among patients who developed AKI, a significant difference was found only in terms of AOPP levels between septic and nonseptic patients. The correlation between endotoxin activity and BNP in septic patients and the increase in the levels of NGAL, BNP, and AOPP in case of sepsis and AKI, in particular if they are associated, indicate a multiorgan involvement in these two conditions.